2004
DOI: 10.1109/mdso.2004.26
|View full text |Cite
|
Sign up to set email alerts
|

MoCA: A Middleware for Developing Collaborative Applications for Mobile Users

Abstract: MoCA the Mobile Collaboration Architecture is a middleware for developing and deploying context-aware collaborative applications for mobile users. It comprises client and server APIs, core services for monitoring and inferring the mobile devices' context, and an object-oriented framework for instantiating customized application proxies.Portable computing devices with wireless communication interfaces such as PDAs or smart phones are becoming more powerful and commonplace. Consequently, demand has increased for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
22

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 8 publications
0
43
0
22
Order By: Relevance
“…Additional insights have been provided by transcriptomic analyses in a number of species, including Pyropia (Uji et al 2013) and Gracilariopsis (Kamiya et al 2011), which have identified sets of genes upregulated in different phases of the life cycle. In Gracilaria, Hydropuntia and Grateloupia, research has focused on the ornithine decarboxylase GiODC gene, which regulates carpospore maturation and liberation (Guzmán-Urióstegui et al 2002, Sacramento et al 2004b, García-Jiménez et al 2009, reviewed in García-Jiménez and Robaina 2015. Variation in the expression of GiODC was observed during cystocarp development with levels reduced in fertile tissue (García-Jiménez et al 2009).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…Additional insights have been provided by transcriptomic analyses in a number of species, including Pyropia (Uji et al 2013) and Gracilariopsis (Kamiya et al 2011), which have identified sets of genes upregulated in different phases of the life cycle. In Gracilaria, Hydropuntia and Grateloupia, research has focused on the ornithine decarboxylase GiODC gene, which regulates carpospore maturation and liberation (Guzmán-Urióstegui et al 2002, Sacramento et al 2004b, García-Jiménez et al 2009, reviewed in García-Jiménez and Robaina 2015. Variation in the expression of GiODC was observed during cystocarp development with levels reduced in fertile tissue (García-Jiménez et al 2009).…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…Besides context management and synchronous querying, CIS also supports context monitoring, allowing clients to register their interest in specific context states (involving one or several context variables) modeled as logical expressions, and to be asynchronously notified whenever the corresponding context-expression is satisfied (or ceases to be satisfied) [5]. For instance, with the expression {"FreeMemory < 10KB" OR "APChange = True"}, an application may subscribe to be notified when the free memory of the device is less than 10KB or when occurs a change of 802.11 network access point.…”
Section: The Moca Architecturementioning
confidence: 99%
“…MoCA architecture [5] has been designed to support the development and deployment of context-aware applications involving mobile devices, and its core services are also adequate for the development and deployment of ubiquitous applications. MoCA's Location Inference Service (LIS) allows to infere the location (and follow the movements) of 802.11-enabled mobile devices within an organization.…”
Section: Introductionmentioning
confidence: 99%
“…This service has been integrated into the MoCA architecture -Mobile Collaboration Architecture [42,31], which allowed us to develop and experiment with some privacy-sensitive and location-aware application prototypes. The main contribution of our work is that we propose a larger, more comprehensible and effective set of privacy control mechanisms that assist the user in building and maintaining her privacy policy.…”
Section: Introductionmentioning
confidence: 99%